2014
DOI: 10.1111/1744-9987.12104
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy and Blood Pressure Control in Automated and Continuous Ambulatory Peritoneal Dialysis Patients

Abstract: Hypertension, non-dipper blood pressure (BP) pattern and decrease in daily urine output have been associated with left ventricular hypertrophy (LVH) in peritoneal dialysis (PD) patients. However, there is lack of data regarding the impact of different PD regimens on these factors. We aimed to investigate the impact of circadian rhythm of BP on LVH in end-stage renal disease patients using automated peritoneal dialysis (APD) or continuous ambulatory peritoneal dialysis (CAPD) modalities. Twenty APD (7 men, 13 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
4
18
0
1
Order By: Relevance
“…Kim et al found that more than 80% ESRD patients had diastolic dysfunction, which might induce insufficiency of renal perfusion and lead to the decreasing of RRF. 6 In this study, we noticed low calcium dialysate preserved RRF by maintaining LV diastolic function. Studies have showed that RRF had beneficial effects on LV hypertrophy and fluid removal.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Kim et al found that more than 80% ESRD patients had diastolic dysfunction, which might induce insufficiency of renal perfusion and lead to the decreasing of RRF. 6 In this study, we noticed low calcium dialysate preserved RRF by maintaining LV diastolic function. Studies have showed that RRF had beneficial effects on LV hypertrophy and fluid removal.…”
Section: Discussionsupporting
confidence: 50%
“…5 The decline of RRF induced extracellular fluid volume overload and hypertension, which resulted in myocardial hypertrophy. 6 However, the relationship of low calcium dialysate and LV diastolic function has not been fully clear until now. In this study, we recruited 60 PD patients and followed up for 12 months, aimed to illuminate the influence of low calcium dialysate on cardiac function in PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Atas, et al reported that a decrease in daily urine volume in PD patients on maintenance APD was associated with LVH. 9) In the current study, LVH was detected in 57.9% of patients and the LVMI was negatively correlated with daily urine volume (r = -0.41, P = 0.03). Recently, Inal, et al reported similar results: 58 percent of PD patients had LVH and the mean LVMI was negatively correlated with daily urine volume in PD patients (r = -0.568, P = 0.001).…”
Section: Discussionsupporting
confidence: 49%
“…8) High PGLI is usually accompanied by glucose absorption from the peritoneal cavity, resulting in harmful effects on glycemic control and lipid profile, and stimulation of the inflammatory process. [9][10][11] These effects appear to be associated with higher mortality. [9][10][11] Diabetes mellitus itself is a major CV risk factor in this population.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation